Pemanfatan Media Moderen dalam Dakwah Islam dengan Pendekatan Religious Marketing - Muhammad Mabrur, Lc., M.Ag (Al-Hiwar : Jurnal Ilmu dan Teknik Dakwah, 2015)
Da'wah is currently facing a world that continues to move forward. He was in the middle of democratization which has guaranteed the rights and freedoms of individuals in behave. Supported by increasingly rapid technological development, particularly in the field of information, which has made it easier for anyone to access a variety of information. So at this point, there is no authority that can compel others to believe or do something. Even religious authorities, nor does it have the power to force anyone, as far as it concerns the behavior or beliefs of a personal nature. It is undeniable that the media have a strong influence in the marketing process. But please note that although the media have an important position, he will not be able to move itself. There are still some other component of 4Ps (Product, Price, Place and Promotion, added Process), which also need to be considered and taken into consideration.